The future of electric vehicles to grid integration in Indonesia. (February 2019) - Huda, Muhammad; Aziz, Muhammad; Tokimatsu, Koji
Abstract: The increasing market share of electric vehicles (EVs) shows a global concern for the climate change. Several policies have been introduced by the government to push EVs development and deployment, such as conventional car purchase restrictions in large cities and subsidies for domestically produced EVs and plug in hybrid electric vehicles (PHEVs). However, the stress to electrical grid becomes a problem when a high penetration of EVs charging demand is occurred. In Indonesian case, as the current capability of the grid to balance its supply and demand is very limited, massive EV charging additionally worsen the condition because of lack of energy storage. Ancillary services of EVs have led to the idea to utilize EVs for supporting the grid, especially as the number of EVs is increasing. The feasibility of vehicle-to-grid (V2G) in Indonesian electrical grid is evaluated in this study. The load levelling and frequency regulation have been focusely observed. The impacts of EVs adoption and V2G participation rates, which are motivated by some incentive from transmission service operator (TSO), are also analyzed. The results show that the power absorbed and released by EVs following their charging and discharging is feasible to support the Indonesian grid if EVs are properly controlled.